2020
DOI: 10.1140/epjc/s10052-020-08570-y
|View full text |Cite
|
Sign up to set email alerts
|

Tidal-charge effects on the superradiance of rotating black holes

Abstract: The changes a (negative) tidal charge causes at the phenomenon of superradiance which occurs around rotating black holes are investigated. This is made by computing the amplification factors of massless scalar waves being scattered by the black hole. It is shown that the increase of the tidal-charge intensity leads to a considerable enhancement of energy extraction from near-extreme black holes. Such improvement results from the fact that extreme black holes with more negative tidal charges spin faster. Maximu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The phenomenon of superradiance was considered in ref. [35]. By computing the amplification factors of massless scalar waves, it was found that the tidal charge considerably enhances the energy extraction from near-extreme black holes.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of superradiance was considered in ref. [35]. By computing the amplification factors of massless scalar waves, it was found that the tidal charge considerably enhances the energy extraction from near-extreme black holes.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of extra spatial dimensions, either through large volume [48,52] or through exponential warping [49,53], can reduce the four dimensional Planck scale to electroweak scale and hence the fine tuning/gauge hierarchy problem can be avoided. Latter studies have shown several other contexts having interesting applications of the higher dimensional scenario, which includes -BHs [54][55][56][57][58][59][60][61][62][63], cosmology [64,65], GWs [17,35,[66][67][68][69][70][71][72][73] among others. In most of these higher dimensional scenario, the effective gravitational dynamics in four dimensions, which is a hypersurface in the full higher dimensional spacetime will be different from that of Einstein gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of extra spatial dimensions, either through large volume [45,49] or through exponential warping [46,50], can reduce the four dimensional Planck scale to electroweak scale and hence the fine tuning/gauge hierarchy problem can be avoided. Latter studies have shown several other contexts having interesting applications of the higher dimensional scenario, which includes -BHs [51][52][53][54][55][56][57][58], cosmology [59,60], GWs [17,35,[61][62][63][64][65][66][67][68] among others. In most of these higher dimensional scenario, the effective gravitational dynamics in four dimensions, which is a hypersurface in the full higher dimensional spacetime will be different from that of Einstein gravity.…”
Section: Introductionmentioning
confidence: 99%